2018
DOI: 10.1175/ei-d-17-0023.1
|View full text |Cite
|
Sign up to set email alerts
|

Predicted Land Carbon Dynamics Are Strongly Dependent on the Numerical Coupling of Nitrogen Mobilizing and Immobilizing Processes: A Demonstration with the E3SM Land Model

Abstract: While coupling carbon and nitrogen processes is critical for Earth system models to accurately predict future climate and land biogeochemistry feedbacks, it has not yet been analyzed how numerical methods that land biogeochemical models apply to couple soil mineral nitrogen mobilizing and immobilizing processes affect predicted ecosystem carbon and nitrogen cycling. These effects were investigated here by using the E3SM land model and an evaluation of three plausible and widely used numerical couplings: 1) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 59 publications
4
20
0
Order By: Relevance
“…Some of them also consider the phosphorus cycle (Goll et al, ; Wang et al, ; Yang et al, ). Although these models were built with the concept that nutrient deficiency limits the carbon cycle, large uncertainties stem from how nutrient limitations are implemented (Medlyn et al, ; Tang & Riley, ; Zaehle et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Some of them also consider the phosphorus cycle (Goll et al, ; Wang et al, ; Yang et al, ). Although these models were built with the concept that nutrient deficiency limits the carbon cycle, large uncertainties stem from how nutrient limitations are implemented (Medlyn et al, ; Tang & Riley, ; Zaehle et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Here we demonstrated how continuous and discrete time approaches can reconstruct soil radiocarbon profiles using only land model 12 C stocks and fluxes and atmospheric 14 C values. We applied the approach here to the ELMv1‐ECA model (Riley et al, ; Tang & Riley, ; Zhu et al, ), which explicitly represents soil organic matter 14 C dynamics with seven soil pools and ten vertical layers, and showed that our approach very accurately reproduces the full model simulations (bias <0.01%). The approach can also be used for the new suite of CMIP6 simulations to evaluate whether the models are accurately representing soil C age and transit time, in addition to soil carbon stock (He et al, ; Lawrence et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Golaz et al () described simulations performed using the fully coupled E3SM at resolution of ~100 km for the atmosphere and land, 30–60 km for the ocean and sea ice, and 0.5° for the river. The E3SM land model (ELM; Drewniak, ; Liang et al, ; Ricciuto et al, ; Tang & Riley, ) was developed from the Community Land Model version 4.5 (CLM4.5; Oleson et al, ) and is coupled to MOSART using one‐way coupling. Each MOSART computational unit (grid) includes subgrid hillslopes, subgrid tributaries, and a single main channel which connects the local grid cell with the upstream/downstream grid cells through the river network.…”
Section: Methods and Datamentioning
confidence: 99%